Championship Sports for Iranian Women: Challenges, Opportunities and Solutions - Nazanin Rasekh; Hossein Zareian; Hamid Ghasemi; Zohreh Rezaie (Allameh Tabataba'i University Press, 2019)
Purpose: The main purpose of this research was to study the challenges, opportunities and solutions of the championship sports for Iranian women. Method: The research method was mixed,and different methods were applied to serve the purpose of this research. The research sample was selected from the main population (N=172) following Morgan's sample size determination (118). Open and closed questionnaires were used to measure the effect of each of the challenges and opportunities with a Likert's five-item scale. Results: The findings showed that 9 opportunities and 19 challenges exist regarding Iranian women's championship sports. Conclusions: Though investigations of women's sports in internal and external fields show progress in Iranian women's sports, they do not show any desirable growth compared to male sports, which isdue to social restrictions and other factors.